The Role of Inclusive Leadership in Enhancing the Strategic Flexibility - Obaid, Hayder Jasim; Al-Abachee, Ali Sahib Flayyih (International Journal of Psychosocial Rehabilitation, 2020)
The paper aims to explore the role of inclusive leadership in its dimensions (openness and communication, support and guidance, accessibility) in improving strategic flexibility with its dimensions (market flexibility, service flexibility provided, and competitive flexibility). The study uses a sample of (162) employees and professors at the University of Kufa. The study used the questionnaire as a main tool to collect data related to the study variables. The goal of the research is to test a number of main and secondary hypotheses related to the relationship of influence and influence between research variables by answering questions related to the study problem. In order to process the data, the study used many statistical methods to reach the results using the program (SMART PLS) and (v.20 SPSS). The results show that leadership practices at the university led to the development of strategies in an attempt to keep pace with changes in the educational environment. These results require strengthening leadership practices that focus on participation and take the views of the professor and employees. Consequently, flexible strategies can be developed that reflect positively on keeping pace with developments in the educational environment.